Pengaruh Ukuran Perusahaan, Umur Perusahaan, Leverage dan Profitabilitas Terhadap Intellectual Capital Disclosure Pada Perusahaan Terdaftar Indeks Sri-Kehati Tahun 2019-2022 - Nur Inayah, Septiani; Difa, Farah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The purpose of this study is to determine the effect of company size, company age, leverage and profitability on intellectual capital disclosure in Sri-Kehati Indexed companies for the 2019-2022 period. This type of research is classified as correlational research with a quantitative approach. The data used is secondary data with the population obtained from the annual financial statements of the Sri-Kehati Index for 2019-2022 from the official website of each company. The sample was selected based on purposive sampling technique and obtained 32 samples of companies during the research period. The data analysis technique uses multiple regression tests with hypothesis testing using the t test and F test. The results showed that company size and company age had an effect on intellectual capital disclosure, while leverage and profitability had no effect on intellectual capital disclosure in companies listed in the Sri-Kehati Index in 2019-2022. This illustrates that the greater and longevity of the company, the more activities are carried out and in general large companies have more business units and have the opportunity to create long-term value so that they will increase the disclosure of information on their intellectual capital.